Apprentice pay in Britain, Germany and Switzerland : institutions, market forces and market power - Ryan, Paul [Verfasser]; Backes-Gellner, Uschi [Verfasser]; Teuber, Silvia [Verfasser]; Wagner, Karin [Verfasser] (My University, 2013)
"The pay of metalworking apprentices is high in Britain, middling in Germany and low in Switzerland. We analyse these differences using fieldwork evidence and survey data, drawing on both economic and institutionalist theories. Several institutional attributes influence apprentice pay, partly by affecting supply and demand in markets for training places. Institutional support for apprenticeship training appears to involve important complementarities in both Germany and Switzerland, in contrast to Britain's less coherent and more market-driven approach." (Authors' abstract, BIBB-Doku)
Keywords: S 2.1.6 Arbeits- & Tarifrecht; S 4.2.1 Personalkosten; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); I 2.2.1 Westeuropa; I 2.1 Deutschland; Ausbildungsvergütung; Einkommensstruktur; Metallberuf; Internationaler Vergleich; Großbritannien; Bundesrepublik Deutschland; Schweiz